Legal Protection Against Leakage of Traveloka Consumer Personal Data by the Company - Lunaraisah, Lunaraisah; Sulistiyono, Adi (International Journal of Educational Research & Social Sciences, 2023)
Abstract. The number of incidents of misuse of personal data for loan applications on the Paylater e-commerce platform is currently caused by the lack of a strict security system in digital companies in Indonesia. Currently, data leakage problems befall Traveloka consumers. Although some of them don't use the pay later feature in the app, they still find it difficult to get approval from banks due to having poor credit scores. This study aims to analyze legal protection efforts provided against misuse of consumer data on the Traveloka PayLater feature. The author uses normative legal research methods with a statutory approach and a conceptual approach analyzed through legal materials. Based on the results of the research, Traveloka as a service provider acts as a collector and manager of consumer data which is obliged to protect the data collected from the beginning until data deletion. Legal protection for consumers can be done both through internal legal protection and external legal protection, Internal legal protection can be done by considering the agreement between consumers and Traveloka companies and it is found that there is an exoneration clause in the agreement so that the agreement can be canceled. Meanwhile, external legal protection can be provided by sanctioning Traveloka as the collector and processor of consumer personal data following the provisions in Law Number 27 of 2022 concerning Personal Data Protection. Keywords: Legal Protection, Personal Data, Traveloka Pay Later.